Polymorphisms in the glucokinase-associated, dual-specificity phosphatase 12 (DUSP12) gene under chromosome 1q21 linkage peak are associated with type 2 diabetes - Das, S; Chu, W; Hale, T; Wang, X; Craig, R; Wang, H; Shuldiner, A; Froguel, P; Deloukas, P; McCarthy, M; Zeggini, E; Hasstedt, S; et al. (2006)
Linkage of type 2 diabetes to chromosome 1q21-q23 is well replicated across populations. In an initial 50-kb marker map (580 markers) across the linked region, one of the two strongest associations observed in Utah Caucasians was at marker rs1503814 (P < 0.00001 in pools, P < 0.004 in individuals). Based on this association, we typed additional markers and screened for sequence variation in the nearby DUSP12 gene. The strongest associations mapped to a highly conserved nongenic sequence just telomeric to rs1503814 and extended 10 kb telomeric through the DUSP12 gene and into the 5′ end of the adjacent ATF6 gene. No coding variant could explain the association in the DUSP12 gene. An extended haplotype encompassing markers from -8,379 to +10,309 bp relative to the ATG start was more common in Caucasian case (0.381) than control subjects (0.285, P = 0.005) and was uniquely tagged by a 194-bp allele at either of two simple tandem repeat variants or by the T allele at marker +7,580. Markers -8,379 and +7,580 were nominally associated with type 2 diabetes in African-American subjects (P < 0.05), but with different alleles. Marker rs1503814 was strongly associated with postchallenge insulin levels among family members (P = 0.000002), but sequence variation in this region was not associated with type 2 diabetes in three other populations of European ancestry. Our data suggest that sequences in or upstream of DUSP12 may contribute to type 2 diabetes susceptibility, but the lack of replication suggests a small effect size. © 2006 by the American Diabetes Association.